Public enterprise in less-developed countries - Jones, Leroy P.; Boston Area Public Enterprise Group (Cambridge [Cambridgeshire] : New York : Cambridge University Press, 1982)
This book examines the size and structure of the public-enterprise sector in mixed economies, with emphasis to those in less-developed countries.
Selected from papers prepared for the 2nd BAPEG conference held in April 1980.
Includes bibliographical references.
oo 27/09/18
Loans
Keywords: Government business enterprises